Intensity-sensitive quality assessment of extended sources in astronomical images - Li, X; Armour, W; Adámek, K (American Astronomical Society, 2024)
Radio astronomy studies the Universe by observing the radio emissions of celestial bodies. Different methods can be used to recover the sky brightness distribution (SBD), which describes the distribution of celestial sources from recorded data, with the output dependent on the method used. Image quality assessment (IQA) indexes can be used to compare the differences between restored SBDs produced by different image reconstruction techniques to evaluate their effectiveness. However, reconstructed images (for the same SBD) can appear to be very similar, especially when observed by the human visual system (HVS). Hence, current structural similarity methods, inspired by the HVS, are not effective. In the past, we have proposed two methods to assess point-source images, where low amounts of concentrated information are present in larger regions of noise-like data. But for images that include extended source(s), the increase in complexity of the structure makes the IQA methods for point sources oversensitive because the important objects cannot be described by isolated point sources. Therefore, in this article we propose the augmented low-information similarity index (augLISI), an improved version of LISI, to assess images including extended source(s). Experiments have been carried out to illustrate how this new IQA method can help with the development and study of astronomical imaging techniques. Note that although we focus on radio astronomical images herein, these IQA methods are also applicable to other astronomical images and imaging techniques.